Co-relation between magnetic resonance imaging and arthroscopy findings in diagnosis of meniscus injuries based on location of the meniscus tear and radial position - Shetty, Chandan; Rathod, Girish; Raut, Nitin; Borole, Pushkar; Gawali, Vijaykumar (International Surgery Journal, 2022)
Background: The objective of our study was to find the sensitivity, specificity of magnetic resonance imaging (MRI) in diagnosing meniscus tears based on its location medial or lateral and radial position namely; anterior 1/3rd, middle 1/3rd, posterior 1/3rd location of the meniscus. Methods: All patients who have undergone arthroscopic surgeries for knee from January 2017 to July 2021 at our institute were retrospectively analyzed through hospital records comparing the MRI findings with the arthroscopy findings, taken as gold standard. Of the 68 patients found from the hospital records 14 patients were excluded as they didn’t qualify as per the inclusion criteria. Results: The sensitivity and sensitivity of MRI in diagnosis of medial meniscus tear was 100% and 50% respectively. The positive predictive value and negative predictive value for medial meniscus was 68%and 100% respectively whereas for lateral meniscus it was 50%and 100%respectively. Based on the radial location of the tear for the medial meniscus the sensitivity of MRI was maximum for middle and posterior 1/3rd medial meniscus tear (100%). For the lateral meniscus the maximum sensitivity was for the middle1/3rd (100%) but specificity and positive predictive value was maximum (100%) for the anterior 1/3rd and posterior 1/3rd tear. Conclusions: The MRI had similar sensitivity and specificity for both the medial and lateral meniscus diagnosis although specificity was low indicating many false positive results from MRI. Middle 1/3rd medial and lateral meniscus tears had poor predictive value.